2023
DOI: 10.1212/con.0000000000001236
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications of Cancer Treatment

Abstract: Objective Advances in cancer treatment have led to extended survival and increased risk of neurologic complications in an aging population. This review summarizes potential neurologic complications in patients who have undergone treatment for neurologic and systemic malignancies. Latest Developments Radiation and cytotoxic chemotherapy along with other targeted therapies continue to be the mainstay of cancer treatment. These advances in cancer care have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…A thorough review of neurologic complications of cancer treatment can be found in the June 2023 issue of Continuum on the neurology of systemic disease. 95 Immune Checkpoint Inhibitor-related Complications Monoclonal antibodies targeting immune checkpoint molecules have changed both the landscape of oncologic care and the spectrum of neurotoxicity syndromes.…”
Section: Spontaneous Intracranial Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…A thorough review of neurologic complications of cancer treatment can be found in the June 2023 issue of Continuum on the neurology of systemic disease. 95 Immune Checkpoint Inhibitor-related Complications Monoclonal antibodies targeting immune checkpoint molecules have changed both the landscape of oncologic care and the spectrum of neurotoxicity syndromes.…”
Section: Spontaneous Intracranial Hemorrhagementioning
confidence: 99%
“…This section focuses on severe neurotoxicity from cancer therapy that presents as a neurologic emergency or can be encountered in the critically ill patient population. A thorough review of neurologic complications of cancer treatment can be found in the June 2023 issue of Continuum on the neurology of systemic disease 95 …”
Section: Treatment-related Complicationsmentioning
confidence: 99%